Mammalian prion protein (PrP) forms conformationally different amyloid intracellular aggregates in bacteria. Issue 1 (December 2015) - Macedo, Bruno; Sant'Anna, Ricardo; Navarro, Susanna; Cordeiro, Yraima; Ventura, Salvador
Abstract Background An increasing number of proteins are being shown to assemble into amyloid structures that lead to pathological states. Among them, mammalian prions outstand due to their ability to transmit the pathogenic conformation, becoming thus infectious. The structural conversion of the cellular prion protein (PrPC ), into its misfolded pathogenic form (PrPSc ) is the central event of prion-driven pathologies. The study of the structural properties of intracellular amyloid aggregates in general and of prion-like ones in particular is a challenging task. In this context, the evidence that the inclusion bodies formed by amyloid proteins in bacteria display amyloid-like structural and functional properties make them a privileged system to model intracellular amyloid aggregation. Results Here we provide the first demonstration that recombinant murine PrP and its C-terminal domain (90–231) attain amyloid conformations inside bacteria. Moreover, the inclusions formed by these two PrP proteins display conformational diversity, since they differ in fibril morphology, binding affinity to amyloid dyes, stability, resistance to proteinase K digestion and neurotoxicity. Conclusions Overall, our results suggest that modelling PrP amyloid formation in microbial cell factories might open an avenue for a better understanding of the structural features modulating the pathogenic impact of this intriguing protein.